Development of a fixed-order $$H_{∞ }$$ controller for a robust P&O-MPPT strategy to control poly-crystalline solar PV energy systems - Moussa Sedraoui; Mohcene Bechouat; Ramazan Ayaz; Yahya Z. Alharthi; Abdelhalim Borni; Layachi Zaghba; Salah K. ElSayed; Yayehyirad Ayalew Awoke; Sherif S. M. Ghoneim (Scientific Reports)
Abstract This paper presents a novel approach to modeling and controlling a solar photovoltaic conversion system(SPCS) that operates under real-time weather conditions. The primary contribution is the introduction of an uncertain model, which has not been published before, simulating the SPCS’s actual functioning. The proposed robust control strategy involves two stages: first, modifying the standard Perturb and Observe (P&O) algorithm to generate an optimal reference voltage using real-time measurements of temperature, solar irradiance, and wind speed. This modification leads to determining and linearizing the nonlinear current-voltage (I-V) characteristics of the photovoltaic (PV) array near standard test conditions (STC), resulting in an uncertain equivalent resistance used to synthesize an overall model. In the second stage, a robust fixed-order $$H_{∞ }$$ controller is designed based on this uncertain model, with frequency-domain specifications framed as a weighted-mixed sensitivity problem. The optimal solution provides the controller parameters, ensuring good reference tracking dynamics, noise suppression, and attenuation of model uncertainties. Performance assessments at STC compare the standard and robust P&O-MPPT strategies, demonstrating the proposed method’s superiority in performance and robustness, especially under sudden meteorological changes and varying loads. Experiment results confirm the new control strategy’s effectiveness over the standard approach.